2017
DOI: 10.22296/2317-1529.2017v19n2p310
|View full text |Cite
|
Sign up to set email alerts
|

The economic and spatial restructuring and development process in the North Sector of the Metropolitan Region of Belo Horizonte, Minas Gerais

Abstract: A b s t r a c t : This aim of this study is to evaluate the economic and spatial restructuring process implemented by the public authorities in the North Sector of the Metropolitan Region of Belo Horizonte, and the appropriation of space by the land and real estate markets in the north and periphery of the capital, seeking to identify the elements that have contributed to altering the land order and to the elitization of spaces. The metropolitan strategic plan sought to diversify the industrial base of the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…She concluded that gentrification already characterised the region (França, 2014: 51), although she had not analysed real estate or demographic datasets, or conducted a residential survey. Diniz and Véras (2017) used real estate asking prices published in local newspapers and tax data to find evidence for increases in land value. They analysed census data for one neighbourhood ( Venda Nova ) in the region.…”
Section: Literature and Framework On Gentrificationmentioning
confidence: 99%
“…She concluded that gentrification already characterised the region (França, 2014: 51), although she had not analysed real estate or demographic datasets, or conducted a residential survey. Diniz and Véras (2017) used real estate asking prices published in local newspapers and tax data to find evidence for increases in land value. They analysed census data for one neighbourhood ( Venda Nova ) in the region.…”
Section: Literature and Framework On Gentrificationmentioning
confidence: 99%